Peran Kepemimpinan Kyai dalam Pembentukan Jiwa Kemandirian dan Entrepreneurship Santri - Anggraeni, Melyvita Nur; Shobirin, Mochammad Syafiuddin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Kiai leadership is a topic that has received a lot of attention from Islamic boarding school observers, because it is one of the factors that determine development. Kiai has the responsibility to not only lead and motivate, but also compose, manage and develop the entrepreneurship curriculum. This research aims to 1) To describe the role of kyai leadership in forming the spirit of independence and entrepreneurship in students. 2) To find out the obstacles and support in forming the spirit of independence and entrepreneurship in students. The location of this research was carried out at the As-Salma Bahrul Ulum Tambakberas Jombang Islamic boarding school. The method used in this research is a descriptive qualitative method. Data collection techniques in this research used observation, interview and documentation techniques. The data analysis techniques used in this research are (1) data reduction; (2) display/presentation of data; (3) draw conclusions and then verify them. The results of this research show that the kiai of the As-Salma Islamic boarding school implemented strategies to shape the students' mental independence and familiarize them with attitudes that can help them master various fields and be able to compete in the future. This can be seen in the students who are trained to have a disciplined attitude and manage their time well, including waking up and praying together. And students are also given a platform for them develop their talents.